2017
DOI: 10.1016/j.idairyj.2016.11.008
|View full text |Cite
|
Sign up to set email alerts
|

Extended-spectrum β-lactamase, shigatoxin and haemolysis capacity of O157 and non-O157 E. coli serotypes from producer-distributor bulk milk

Abstract: We investigated for virulence genes (stx1, stx2 and hlyA), serotypes and extended-spectrum βlactamases (ESBLs) producing capacity in O157 and non-O157 Escherichia coli isolated from producer-distributor bulk milk (PDBM). Fifteen different E. coli O-serogroups were observed from the isolates (n=121). The prevalence of stx1 and stx2 genes among the E. coli isolates was 8.3% and 11.6% (n=121), respectively, while 5.8% harboured both stx1 and stx2. Four E. coli isolates (3.3%) had ESBLs producing capacity, resiste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
18
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

5
1

Authors

Journals

citations
Cited by 11 publications
(23 citation statements)
references
References 54 publications
2
18
0
Order By: Relevance
“…The first study was initiated by The South African Department of Agriculture and Water Research Commission to help characterize the bacterial quality of South African irrigation water (Aijuka et al, 2015). A high prevalence of faecal indicators within milk sold by unregulated retailers alarmed the South African Dairy Development Agency which subsequently initiated the second study to characterize its microbiological quality (Ntuli et al, 2017(Ntuli et al, , 2016.…”
Section: Introductionmentioning
confidence: 99%
“…The first study was initiated by The South African Department of Agriculture and Water Research Commission to help characterize the bacterial quality of South African irrigation water (Aijuka et al, 2015). A high prevalence of faecal indicators within milk sold by unregulated retailers alarmed the South African Dairy Development Agency which subsequently initiated the second study to characterize its microbiological quality (Ntuli et al, 2017(Ntuli et al, , 2016.…”
Section: Introductionmentioning
confidence: 99%
“…and pasteurized PDBM samples, from all the provinces in SA, reported in previous studies by Ntuli et al (44,45) were incorporated in the estimation of STEC concentration. The studies reported STEC prevalence of 11.0 and 7.7% in raw and pasteurized PDBM samples from all the provinces in SA, respectively.…”
Section: Estimation Of Stec Concentration In Pdbm Data On the Prevalmentioning
confidence: 99%
“…Shigatoxin producing E. coli O157:H7 is still recognized as epidemiologically significant world-wide, however, in some geographical regions, non-O157 STEC (O26, O103, O111 and O145) are becoming prominent as important E. coli pathotypes (13,28). Recent reports on raw and pasteurized PDBM in South Africa (SA) indicated prevalence of STEC O157 and non-O157 ranging from 10 -54% (5,36,44,45). Ntuli et al (45) documented emerging non-O157 STEC O2, O9, O20, O43, O64, O68, O83, O112, O155 and O157 in PDBM in SA.…”
mentioning
confidence: 99%
See 2 more Smart Citations